Long‐term outcomes of catheter ablation of ventricular tachycardia in patients with structural heart disease. Issue 1 (3rd July 2014) - Goya, Masahiko; Fukunaga, Masato; Hiroshima, Ken‐ichi; Hayashi, Kentaro; Makihara, Yu; Nagashima, Michio; An, Yoshimori; Ohe, Seiji; Yamashita, Kennosuke; Ando, Kenji; Yokoi, Hiroyoshi; Iwabuchi, Masashi; et al.
Abstract: Background: Catheter ablation of ventricular tachycardia (VT) is feasible. However, the long‐term outcomes for different underlying diseases have not been well defined. Methods: Eighty‐eight consecutive patients who underwent catheter ablation of VT using a three‐dimensional mapping system were analyzed. The primary endpoint was any VT or ventricular fibrillation (VF) recurrence. Secondary endpoints were a composite of death or any VT/VF recurrence. Underlying heart diseases were remote myocardial infarction (remote MI) in 51 patients and non‐ischemic cardiomyopathy in 37 (arrhythmogenic right ventricular cardiomyopathy [ARVC] in 18 patients, and dilated cardiomyopathy [NIDCM] in 19). Results: Acute success was achieved in 82 of 88 (93%) patients. During a follow‐up period of 39.2±4.6 months, VT recurred in 26 of 87 (30%), and VT/VF recurrence or death occurred in 39 of 87 (45%) patients. ARVC had better outcomes than NIDCM for the primary ( p <0.05) and secondary endpoints ( p <0.05). Remote MI‐VT revealed a midrange outcome. Conclusions: The long‐term outcomes after catheter ablation of VT varied according to the underlying heart disease. ARVC‐VT ablation was associated with better long‐term prognosis than NIDCM. Remote MI‐VT demonstrated a midrange outcome.